2018
DOI: 10.1002/qua.25706
|View full text |Cite
|
Sign up to set email alerts
|

Global and local reactivity descriptors based on quadratic and linear energy models for α,β‐unsaturated organic compounds

Abstract: Global and local descriptors of chemical reactivity can be derived from conceptual density functional theory. Their explicit form, however, depends on how the energy is defined as a function of the number of electrons. Within the existing interpolation models, here, the quadratic and the linear energy model were used to derive global descriptors as the electrophilicity and nucleophilicity (defined as the negative of the ionization potential) and local descriptors employing either the corresponding condensed Fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…In our previous study, we have shown that the condensed Fukui functions under the fragment molecular response (FMR) approach with the Hirshfeld-I partitioning method correctly describe the reactivity of α,βunsaturated systems such as the crotonyl thioester. 33 Recently, our findings were further independently confirmed by others. 34,35 Here we use the validated local reactivity descriptor to analyze the crotonyl test system in different conformations and molecular environments such as a vacuum, aqueous solution, and the enzyme.…”
Section: ■ Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our previous study, we have shown that the condensed Fukui functions under the fragment molecular response (FMR) approach with the Hirshfeld-I partitioning method correctly describe the reactivity of α,βunsaturated systems such as the crotonyl thioester. 33 Recently, our findings were further independently confirmed by others. 34,35 Here we use the validated local reactivity descriptor to analyze the crotonyl test system in different conformations and molecular environments such as a vacuum, aqueous solution, and the enzyme.…”
Section: ■ Introductionsupporting
confidence: 82%
“…For each configuration of the atoms the reactivity of the crotonyl thioester as the enzyme substrate model was studied with atom-condensed local reactivity descriptors based on conceptual DFT. In our previous study, we compared several global and local reactivity descriptors for this family of molecules with the result that the atom-condensed Fukui function within the linear energy model best reproduces the experimental electrophilicity and nucleophilicity of α,β-unsaturated esters, amides, and thioesters …”
Section: Methodsmentioning
confidence: 99%
“…In addition, conceptual DFT (Figure S3, Table S2 and S3) of MTFA was calculated . The condensed values of the Fukui functions f + showed carbonyl carbon display a larger value with respect to the methyl carbon, illustrating that carbonyl carbon of MTFA is more electrophilic . Therefore, the carbonyl carbon possesses higher positive charge than methyl carbon, and the carbonyl group of MTFA is a harder electrophile and the methyl group represents softer electrophile.…”
Section: Methodsmentioning
confidence: 99%
“…Electronic properties of the reactants and TSs were calculated with the B3LYP/6-31+G(d) level of theory and used as features for the models. Reactant features were ionization energies; electron attachment energies 222 ; the surface electrostatic potential and electrostatic potentials at reactive nuclei 223,224 ; local and global descriptors of nucleophilicity and electrophilicity 225 ; atomic charges; bond orders; solvent accessible surface areas 226 ; and a descriptor for dispersion. 227 TS features were the activation barrier of the reaction as calculated with the ωB97X-D/6-311+G(d,p) level of theory; TS atomic charges; TS bond orders; and TS nuclear electrostatic potentials.…”
Section: Reducing Data Requirements and Interpreting Modelsmentioning
confidence: 99%